تحلیل جای‌گاه رفتار اخلاقی در آثار داستانی یعقوب یاد علی با تکیه بر آموزه‌های ژاک لکان - Tayefi, Shirzad; Shalchian Nazer, . Tohid (Ghālib (Kabul, Afghanistan), 2024)
Jacques Marie Émile Lacan was one of the thinkers who reread the category of ethics based on psychoanalytical doctrine. He considered adherence to the sign of desire as a criterion for ethical behavior. In this research, we have tried to evaluate the actions of the characters in Yaqoub Yad Ali's fictional works according to the psychoanalytic teachings of Lacan. Based on this, it is necessary to explain the relationship between the place of desire as a psychological matter and ethic. One of the goals of the authors in this research is to explain the distinction between the desire of the subject and The Other as an irreconcilable divergence. In this regard, the question has been answered that based on Lakan's psychoanalytical teachings, which one of Yad Ali's fictional characters had an ethical action, and which one had an immoral action? This research has been done by qualitative analysis based on the teachings of Lacan and the collection of fiction works of Yaqub Yad Ali. The findings of the research show that the establishment of the desire suppression mechanism causes the subject to encounter the phenomenon of loss or deprivation. The subject identifies the signifier of The Other’s desire as the signifier of his desire and fulfills it. According to Lakan, the ethical behavior becomes possible when the subject always remains faithful to the signifier of his true desire. The ethical subject in Lakan's view is the one who, in the face of the law, always transgresses it through the sign of joesance